Enhancing cation exchange capacity of chars through ozonation. (October 2015) - Smith, Matthew; Ha, Su; Amonette, James E.; Dallmeyer, Ian; Garcia-Perez, Manuel
Abstract: The use of ozone to increase the cation exchange capacity (CEC) of two chars produced from pyrolysis of Douglas fir ( Pseudotsuga menziessii ) and a control bituminous coal activated carbon (AC) is reported. Chars were produced from the wood fraction of Douglas fir (DFWC) and the bark (DFBC) at 500 °C using an auger driven reactor with a nitrogen sweep gas under mild vacuum. Five ozone treatment times, ranging from 5 min to 60 min, were investigated. The initial properties of each char were found to differ significantly from the other samples in terms of surface area, proximate composition, and elemental composition. DFWC did not show significant mass loss or temperature variation during ozone treatment; however, after 1 h of oxidation both DFBC and AC samples resulted in 20% and 30% mass loss, respectively, and reactor temperatures in excess of 60 °C. Analysis of the pore size distribution of each treatment shows that ozone treatment did not significantly affect small micropores after 30 min of treatment for any material, but did reduce the apparent surface area of mesopores. Increases in carboxylic groups were identified with ozone treatment and found to correlate strongly with changes in measured CEC. The formation of lactone was found to correlate positively with reactor temperature during oxidation. These results indicate that the properties of chars, including surface area, pore structure, and chemical composition, as well as reactor conditions strongly affect the ozone oxidation of chars. Highlights: Char from Douglas fir wood and bark, as well as a commercial activated carbon have been oxidized via high concentration ozone. Changes in surface area, bulk oxygen content, and surface oxygen groups have been examined. Effect of oxidation on the pH at the point of zero charge and the cation exchange capacity have been measured. Ozone treatment was found to generate carboxylic and lactonic groups on both char and activated carbon. Carboxylic acid groups have been linked to increased CEC.